The role of online learning environment on the students' basic psychological needs satisfaction during the Covid-19 pandemic - Aditia, Gilang Rizkia; Dahlan, Tina Hayati; Ilfiandra, Ilfiandra (International Journal of Research in Counseling and Education, 2021)
The transition of learning systems during pandemic is one of the factor causing the inability to fulfill psychological basic needs satisfaction that are oriented on the low level of student self-determination such as self-regulation, self-confidence and responsibility. The focus of study in this article to explain the role ofonline learning process towardstudents’ autonomy, competence and relatedness satisfaction based on the perspective of cognitive evaluation theory. This theory is used to find out how the online learning environment can facilitate and support students’ basic psychological needs satisfaction and the intrinsic motivation level influenced by exsternal, interpersonal and intrapersonal factors. The method in this article used narrative literature review. Through a literature review, researcher can determine what factors can build student self-determination in online learning process. The findings showed social context and teacher facilitating in online learning environment play important in encouraging and maintain students intrinsic motivation to fulfill the level of students’ autonomy, competence and relatedness satisfaction in doing online learning activity.